The Very Best of Hugh Tracey: from the monumental cd series 'Historical Recordings by Hugh Tracey'. SWP Records. SWP034/HT022. Compiled by Michael Baird in collaboration with ILAM. One compact disc, no accompanying booklet. Lesotho Calling: Lesiba and Sekhankula Music. SWP Records. SWP 033. Recorded and compiled by Michael Baird in collaboration with Dada Moqasa of Lesotho Broadcasting. One compact disc, with 22-page booklet and notes by Michael Baird. - Lobley, Noel (International Library of African Music, 2008)
pages: 129-133
Keywords: African Music; Lesotho